The effect of sulfamethoxazole on oxidative stress indices in zebrafish (Danio rerio) - Tokanová, Nina; Dobšíková, Radka; Doubková, Veronika; Blahová, Jana; Svobodová, Zdeňka; Maršálek, Petr (Drug and chemical toxicology, 2021)
The aim of this study was to assess the impact of sulfamethoxazole (SMX) on oxidative stress indices in zebrafish (Danio rerio). The test was completed after 14 days. The tested concentrations were 50, 100 and 500 µg/L of SMX. Glutathione peroxidase, glutathione reductase, glutathione S-transferase and lipid peroxidation were investigated to determine the effects of SMX on oxidative stress in zebrafish. Lipid peroxidation gradually increased slightly (but non-significantly) at all tested concentrations during the test as compared to the control. The evaluation of oxidative stress biomarkers showed no significant changes in the activity of antioxidant enzymes in any experimental group exposed to SMX as compared to the control. The gradual increase in lipid peroxidation after 3 and 14 days in the SMX treated groups as compared to the control group indicates increasing cell membrane damage.
Keywords: oxidative stress; antioxidancia; TBARS; zvířata; Antioxidants; antibakteriální látky; oxidační stres; Time Factors; antioxidant enzymes; Zebrafish; Lipid Peroxidation; sulfamethoxazol; dánio pruhované; Oxidative Stress; Fish; časové faktory; Sulfamethoxazole; peroxidace lipidů; Animals; Anti-Bacterial Agents; antibiotics